Methodological foundations of public regulation in the sphere of human development under the transformation of the ukrainian society - Pospielova Tetiana (Borys Grinchenko Kyiv Metropolitan University, 2015)
The article deals with the initial methodological prerequisites for the formation of the conception of complex mechanism of public regulation in the sphere of human development under the transformation of the Ukrainian society based on the simultaneous combination of the achievements of the institutional theory and systematic and synergetic approach. Thus there singled out the three components of the institutional environment of human development: formal rules; informal rules; attractive self-organizing structures. It is proved that it is necessary to investigate and consider both formal rules and informal ones and self-organizing attractive structures as well in the process of elaborating a complex mechanism of public regulation in the sphere of human development. Formal rules are analyzed by studying normative legal documents concerning human development. The research of informal rules and self-organizing attractive structures is conducted through socio-cultural dimension. The Ukrainian national methods of calculating the index of regional human development is based on the measurement of external (or objective) factors that mostly characterize the socio-demographic and socio-economic components of human potential. However, subjective factors (valuable and motivational basis of human development and self-organizing processes of institutional environment) that characterize the sociocultural and activity-based components of human development, are not investigated sufficiently. The author proposes to improve methods for human development assessment by introducing additional indicators that characterize the valuable and motivational basis of human development and self-organizing processes derived from sociological observations, namely: main socio-psychological features of a social character; the level of satisfaction with various aspects of life; priorities in life and the importance of professional and social activities; socially significant values.